Video games, crime and control: getting played - Grubb, Jonathan A.; Steinmetz, Kevin F. (Routledge studies in crime, media and popular culture, 2024)
"Discussing the state of play in contemporary popular culture, specifically the role of crime and crime control in the video game medium, this book discusses the criminological importance of video games. Pulling together an international group of scholars from Brazil, Canada, Sweden, the United Kingdom, and the United States, this edited volume analyzes a wide range of noteworthy video games, including Bioshock, Death Stranding, Diablo 2, Beat Cop, The Last of Us, Disco Elysium, Red Dead Redemption, P.T., Spider-Man, Spider-Man: Miles Morales, Star Wars Jedi: Fallen Order, and Grand Theft Auto. The book thus seeks to advance dialog on video games as important cultural artifacts containing significant insights regarding dominant perceptions, interests, anxieties, contradictions, and other matters of criminological interest. Covering policing, vigilantism, different forms of violence, genocide, mental illness, and criminological theory, Video Games, Crime and Control will be of great interest to students and scholars of Criminology, Media Studies, and Sociology, specifically those focusing on Game Studies and Cultural Criminology"--